Análise dos limites e possibilidades da ordem pública processual na homologação de sentença estrangeira pelo STJ - Furtado, Maria Priscila Mendonça (2013)
In principle, a foreign judgment will be recognized and enforced in Brazil after it passed a specific compliance procedure for the homologation of foreign sentence in the Brazilian Superior Court of Justice (“STJ”), regardless of the country in which the foreign judgment was issued. The compliance requirements for the homologation are established in the articles 15 to 17 of the LINDB, which are reproduced, with minor changes, in the articles 5o and 6o of the Resolution no 9 of the STJ. According to such regulations, pubic policy is one of the compliance requirements for the homologation of the foreign sentences in Brazil. One of the issues demonstrated throughout this thesis is the need to establish a more precise definition of procedural public policy, specially when it is applied as one of the compliance requirements in the procedure for the homologation of the foreign sentences by the STJ, noting, therefore, the limits of that concept both within national and international law